Esmalte contendo óleo essencial de Lippia sidoides Cham. para tratamento de onicomicose: caracterização físico-química, atividade antifúngica e avaliação clínica - Sousa, Erik Melo de (2025)
Onychomycosis is a fungal infection of the keratinized nail tissue, mainly caused by dermatophytes, Candida spp., and, less frequently, by non-dermatophyte filamentous fungi. The increasing resistance of fungi to conventional treatments has driven the search for more effective and natural therapeutic alternatives. The essential oil of Lippia sidoides Cham. (OELS), known for its antimicrobial properties, emerges as a promising option, especially against fungi such as Candida albicans and dermatophytes. Therefore, this study aimed to develop, characterize, and clinically evaluate a nail polish formulation containing 8% OELS. The essential oil was extracted from the aerial parts of the plant using steam distillation, followed by the preparation of the nail polish and physicochemical characterization tests, including: drying time, non-volatile content, water resistance, appearance, pH, density, thymol quantification, centrifugation test, organoleptic evaluation, and stability study. The antifungal activity was evaluated in vitro using the agar diffusion method against Candida albicans, and through a phase I clinical trial with 20 healthy volunteers over 90 days, in which clinical and laboratory parameters were monitored. The essential oil yielded an average of 0.89%. The nail polish showed a drying time of 5 minutes and 16 seconds, non-volatile content of 24.2%, water resistance of 28.26%, characteristic appearance, pH of 5.96, density of 1.03171 mg/mL, thymol content of 86.82%, no phase separation during centrifugation, organoleptic characteristics consistent with the plant, and satisfactory stability (8.6% reduction in accelerated stability and 1.62% in long-term stability, compared to the initial concentration). The antifungal activity showed an average inhibition halo of 3.03 ± 0.25 mm against C. albicans. In the clinical study, no significant laboratory alterations or adverse events were observed, indicating product safety. In conclusion, the nail polish containing 8% OELS demonstrated appropriate physicochemical properties, antifungal activity against Candida albicans, and a favorable safety profile for topical use, suggesting it as a promising candidate for the adjunct treatment of nail fungal infections.